Development of Word Wall Learning Media to Support Sentence-Building Skills in Grade II Elementary School Students at SDN 09 Sitiung - Ana Novitasari; Yulia Darniyanti; Aina Ulfa (The Future of Education Journal, 2025)
This research is based on learning at SDN 09 Sitiung, precisely in class II, it was found that student literacy was still low, especially in the Indonesian Language subject. During the learning process, the media used were only teacher books and student books so that the learning process became uninteresting or boring for students in learning. This study aims to develop Word Wall Media in Indonesian Language Subjects to overcome this problem. Word Wall learning media is a media that helps students understand the material. This study aims to produce learning media that can facilitate students in understanding Indonesian language material and can improve students' knowledge of literacy. This study uses the ADDIE model (Analysis, Design, Develop, Implementation, Evaluation). Data collection techniques use validation sheets to see validity, student and teacher response questionnaire sheets to assess practicality. The results of the research that has been conducted indicate that the Wall of Words learning media meets the valid criteria, the percentage of expert assessment results from language experts is 82%, meets the valid criteria, the percentage of expert assessment results from language experts is 82%, the percentage of media experts is 87%, the percentage of question experts is 80%, the percentage of material experts is 82% and the category is valid. Based on the percentage of teacher response questionnaire results, 100% are in the practical category, the category is very practical. Based on these results, the Wall of Words learning media in Indonesian language learning meets the criteria for feasibility and practicality, so it can be used in learning